Reactive Multifunctional Template-Induced Preparation of Fe-N-Doped Mesoporous Carbon Microspheres Towards Highly Efficient Electrocatalysts for Oxygen Reduction - Meng, Fan-Lu; Wang, Zhong-Li; Zhong, Hai-Xia; Wang, Jun; Yan, Jun-Min; Zhang, Xin-Bo (Advanced materials (Weinheim), 2016)
A novel in situ replication and polymerization strategy is developed for the synthesis of Fe‐N‐doped mesoporous carbon microspheres (Fe‐NMCSs). This material benefits from the synergy between the high catalytic activity of Fe‐N‐C and the fast mass transport of the mesoporous microsphere structure. Compared to commercial Pt/C catalysts, the Fe‐NMCSs show a much better electrocatalytic performance in terms of higher catalytic activity, selectivity, and durability for the oxygen reduction reaction.